2017
DOI: 10.1063/1.4983140
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of self-generated magnetic fields in an inertial fusion hohlraum environment

Abstract: We present radiation-hydrodynamic simulations of self-generated magnetic field in a hohlraum, which show an increased temperature in large regions of the underdense fill. Non-parallel gradients in electron density and temperature in a laser-heated plasma give rise to a self-generated field by the “Biermann battery” mechanism. Here, HYDRA simulations of three hohlraum designs on the National Ignition Facility are reported, which use a partial magnetohydrodynamic (MHD) description that includes the self-generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 33 publications
(38 reference statements)
1
51
0
Order By: Relevance
“…By changing the laser spot radius and keeping the intensity constant, the experiment could be scaled into the non-local transport regime, increasing the relevance of the measurements to laser-plasma interaction regimes in ICF drive 5,6,26 and MagLIF pre-heat 1 . A further investigation of this transition will be the subject of a further publication comparing kinetic and MHD results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By changing the laser spot radius and keeping the intensity constant, the experiment could be scaled into the non-local transport regime, increasing the relevance of the measurements to laser-plasma interaction regimes in ICF drive 5,6,26 and MagLIF pre-heat 1 . A further investigation of this transition will be the subject of a further publication comparing kinetic and MHD results.…”
Section: Discussionmentioning
confidence: 99%
“…Even initially unmagnetised ICF configurations can be affected by extended-MHD phenomena, with self-generated fields growing through the Biermann battery process. Simulation studies have found the Nernst (magnetic fields moving down temperature gradients) and Righi-Leduc (heat-flow deflected by the magnetic field) terms to change plasma properties in hohlraums (increasing the temperature of the hohlraum gas fill 5 ), direct-drive ablation fronts (changing the perturbation growth 6 ) and at the compressed fusion-fuel edge (modifying the cooling process 7 ). In addition to a) Electronic mail: c.walsh14@imperial.ac.uk ICF, extended-MHD affects laboratory astrophysics experiments, such as the measurement of magnetic fields generated around laser-foil interactions 8,9 and are anticipated to also affect 2-spot magnetic reconnection 10 .…”
Section: Introductionmentioning
confidence: 99%
“…We conclude that under simplified conditions, nonlocality can in principle account for the observations, but in reality it may play a complementary role and other contributing processes should be considered, most notably magnetic fields [7,8]. MHD simulations suggest the ∇n e × ∇T e mechanism will generate magnetic fields strong enough to inhibit heat flow between the dots.…”
mentioning
confidence: 81%
“…Highly averaged atomic models for calculating ionization balance provide results of comparable accuracy to detailed models but at much lower computational cost [6]. Magnetohydrodynamic (MHD) effects are generally modeled using a fluid expression of Ohm's law [7,8] but models which include both MHD and flux-limited heat transport are not readily available or tested. The lack of experimental data available for testing each of these reduced models presents a significant need in HED physics.…”
mentioning
confidence: 99%
See 1 more Smart Citation